Determinación de la presencia de sarcoptes scabiei en perros (Canis lupus familiaris) en la ciudadela Las Malvinas del cantón Baba - Murillo Alava, Estefanía Juleysi (2025)
This study aimed to determine the presence of Sarcoptes scabiei in dogs, which is responsible for causing sarcoptic mange. This is a globally distributed parasitic dermatosis that affects various mammals, including dogs and humans. This study aimed to determine the prevalence of S. scabiei in canines with dermatitis in the Baba Canton and identify associated risk factors. A total of 40 dogs with clinical signs of dermatitis were examined using deep skin scrapings to identify the mite under a microscope. Data analysis included the evaluation of prevalence rates and the exploration of correlations with variables such as breed, age, and sex. Understanding the epidemiology of Sarcoptes scabiei in this region is crucial for developing effective prevention and control strategies, benefiting both animal and public health. In this study, negative or positive cases were determined according to sex, age, and breed. The research provides relevant information for the management and control of these dermatoses, contributing to improved animal health and healthcare efficiency. Of the 40 dogs examined, 4 were found to be positive for the Sarcoptes scabiei mite. The results showed that 4 dogs (10%) tested positive for the mite, while 36 dogs (90%) tested negative. This analysis reflects a low prevalence of Sarcoptes scabiei in the canine population studied.